Suture Removal After Trabeculectomy With Fornix-based Conjunctival Flap Leads to Faster Visual Recovery but Not Reduced Astigmatism. Issue 5 (May 2019) - Laspas, Panagiotis; Leichsenring, Verena; Hoffmann, Esther; Preussner, Rolf; Wahl, Jochen; Pfeiffer, Norbert
Abstract : Précis: The closing limbal suture after trabeculectomy with a fornix-based conjunctival flap plays no critical role in the development of corneal astigmatism and intraocular pressure (IOP). A standard removal is not recommended. Purpose: To investigate the effect of removal of the conjunctival suture after trabeculectomy with fornix-based conjunctival flap on corneal astigmatism, visual acuity, and IOP. Methods: Eighty-seven cases of trabeculectomy with mitomycin C with a fornix-based conjunctival flap performed in the eyes of 82 patients (5 patients underwent bilateral trabeculectomy) were enrolled in a prospective randomized study. All surgeries were conducted by the same surgeon (J.W.) in the Ophthalmology Department of the University Medical Center of Mainz, Germany. All eyes received a corneal-conjunctival, continuous, mattress, interlocked suture for closing the conjunctiva at the limbus. After randomization, in 46 cases the suture was removed 6 weeks postoperatively; in 41 patients, the suture was left in place. All patients were examined preoperatively, and at 6 weeks, 3 months, 6 months, and 12 months after surgery. Astigmatism was measured using objective refraction and corneal topography, IOP and visual acuity were also assessed. Results were compared using a Wilcoxon test or Mann-Whitney U test for single time-points. Results: During follow-up, no significant differences between the 2 study groups regarding refractive or topographic values were found. Patients in the suture removal group had a significantly higher visual acuity than controls at 3 months, 6 months, and 1 year after surgery. IOP was similar in both groups throughout the study. Conclusions: Removal of the conjunctival suture in trabeculectomy with a fornix-based conjunctival flap leads to a faster rehabilitation of visual acuity but does not significantly affect corneal astigmatism or IOP.